2017
DOI: 10.3340/jkns.2017.0211
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study with Cage-Only or Cage-with-Plate Fixation in Anterior Cervical Discectomy and Interbody Fusion of One and Two Levels

Abstract: ObjectiveThe authors prospectively analyzed the effect of one-level or two-level anterior cervical discectomy and fusion (ACDF), comparing stand-alone cages and cage-with-plate fixation constructs with respect to clinical outcomes and radiologic changes.MethodsA total of 84 patients who underwent one-level (n=52) or two-level ACDF (n=32) for cervical disc disease and who completed 2 years of follow-up were included in this study. The patients were divided by cervical level and grouped into ACDF-Cage-only and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…In a study by Kim et al ., who similarly evaluated ACDF with cage-only and ACDF-CP in one level and two levels, postoperative NDI in cage-only in one level group was lower than the CP group. [ 10 ] Comparison of NDI after surgery in two levels did not demonstrate significant differences in both groups. These findings are consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In a study by Kim et al ., who similarly evaluated ACDF with cage-only and ACDF-CP in one level and two levels, postoperative NDI in cage-only in one level group was lower than the CP group. [ 10 ] Comparison of NDI after surgery in two levels did not demonstrate significant differences in both groups. These findings are consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 94%
“…[ 9 ] The presence of the plate helps maintain the stability of the fusion structure, and the CA method is more beneficial in terms of ease of use plus reducing surgical time and blood loss. [ 10 ] Comparison of CA with CP has revealed different results in several studies. Some studies have shown higher levels of fusion and decreased subsidence levels in the CP technique than the CA method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsidence was defined as a decrease of ASH by more than 2 mm on the lateral radiographs during the follow-up period 6,13) . The SCA was measured as the angle between the superior endplate of the upper vertebra body and the lower endplate of the lower vertebra body.…”
Section: Radiographic Assessmentmentioning
confidence: 99%
“…The necessity, however, of this technique has been questioned over the years since similar results can be achieved employing the stand-alone technique, especially in one- or two-level surgery. [ 2 3 ] The article aims to assess the fusion rates (FRs) and long-term outcomes following three-level ACDF without the use of an anterior plate.…”
Section: Introductionmentioning
confidence: 99%